[PP.34.35]: AGGRESSIVE BLOOD PRESSURE REDUCTION AND STROKE OUTCOMES IN THE VERY ELDERLY. (June 2015) - Brescacin>, L.>; Alonzo, C.; Zurru, M.C.; Colla, P.; Baroni, M.V.; Camera, L.; Cristiano, E.; Waisman, G.
Abstract : Objective: Optimal blood pressure target in the very elderly (> 80 years) is still a matter of debate, even more in the secondary vascular prevention setting. We aim to compare the effect of aggressive blood pressure reduction on early stroke outcomes between very elderly and younger counterparts. Design and method: Acute ischemic stroke patients were prospectively included in PROTEGE-ACV, a multidisciplinary secondary stroke prevention program. Demographic data and pre-stroke vascular risk factor profile and control were obtained from electronic medical records. For the purpose of the analysis, stroke outcomes (cognition by MMSE and clock-drawing test –CDT– and functional status by Barthel index and m-Rankin scale) were analyzed according to 30-day SBP and DBP quintiles in older and younger than 80 years. Results: 516 (42%) of 1215 stroke patients included between December 2006 and December 2013 were older than 80 years. These patients had higher prevalence of hypertension (85% vs 78%, p 0.001), atrial fibrillation (20% vs 9%, p 0.001), chronic kidney disease (44% vs 19%, p 0.0001), were more likely to be female (65% vs 47%, p 0.0001), to have a severe stroke (NIHSS 4 ± 5 vs 2 ± 4, p 0.001) mainly cardioembolic (33% vs 18%, p 0.0001), and to receive antiplatelets (49% vs 38%, p 0.0001), antihypertensives (81% vs 70%, p 0.0001) and anticoagulants (13% vs 6%, p 0.0001) in the year before the stroke. Stroke outcomes are shown in the table. Figure. No caption available. Conclusions: Aggressive blood pressure reduction was associated to worst stroke outcomes in the very elderly patients of our cohort. HYVET trial established the safety and efficacy of 150/80 mmHg as blood pressure target in this population, similar objectives seem to be desirable for secondary stroke prevention.